Statistics for business : data analysis and modeling - Cryer, Jonathan D.; Miller, Robert B. (California : Duxbury Press, 1994)
Statistics for Business: Data Analysis, authors Robert Stine and Dean Foster of the University of Pennsylvania$1 (Bs Wharton School, take a sophisticated approach to teaching statistics in the context of making good business decisions. The authors show students how to recognize and understand each business question, use statistical tools to do the analysis, and how to communicate their results clearly and concisely. In addition to providing cases and real data to demonstrate real business situations, this text provides resources to support understanding and engagement.s
Includes bibliography and index
Keywords: Management -- Statistical methods; Commercial statistics; Business -- Mathematical models